The Impact of Technology Adoption on Efficiency and Transparency in Public Procurement Processes in Kenya - Nebert Ombajo Mandala; Ayoyi Isaac Renson; Too Samson Kipketer (European Scientific Journal, ESJ, 2024)
In recent years, global public procurement has witnessed a paradigm shift with the integration of technology, a phenomenon embraced by countries like Kenya. The Kenyan government has actively modernized its procurement system through the adoption of e-procurement systems, blockchain, and artificial intelligence, aiming to bolster efficiency and transparency. The purpose of this research work was to assess the impact of technology adoption on efficiency and transparency in public procurement processes in Kenya. This research addressed a critical gap in understanding the nuanced impacts of these technological advancements on the intricate dynamics of public procurement in Kenya. Investigating the adoption's influence on efficiency and transparency, the study explored experiences, challenges, successes, and overall implications. The findings are of significance to public governance, offering insights to policymakers, practitioners, and technology developers. Aligned with global sustainable development initiatives, the study advocated for digital literacy training, cybersecurity measures, infrastructure improvement, policy incentives, a national digital procurement strategy, private sector collaboration, policy reviews, and data-sharing initiatives. By embracing the recommendations, Kenya can navigate challenges and capitalize on technology for an efficient, transparent, and resilient future in public procurement, aligning with the United Nations Sustainable Development Goals.